Indium-111 Capromab Pendetide (ProstaScint®) Demonstrates Renal Cell Carcinoma and Aortocaval Nodal Metastases from Prostate Adenocarcinoma - Tanvir Rizvi; Chunli Deng; Patrice Rehm (World Journal of Nuclear Medicine)
A 62-year-old male with a history of radical prostatectomy for a Gleason 9 (4 + 5) pT3N0Mx prostate cancer presented with rising prostate-specific antigen of 9.0 ng/dl. A contrast-enhanced computerized tomography (CT) revealed an enhancing left upper pole renal mass and aortocaval lymph nodes. Indium (In)-111 Capromab Pendetide (ProstaScint ® ) single-photon emission computerized tomography-CT showed abnormal increased uptake in left renal mass and aortocaval lymph nodes with no uptake in the prostate bed or pelvic lymph nodes. He underwent left radical nephrectomy and dissection of aortocaval lymph nodes. Pathology showed renal clear cell carcinoma and metastatic prostate adenocarcinoma involving aortocaval lymph nodes. Our case demonstrates a rare combination of two different malignancies, prostate cancer and clear cell renal cell cancer, showing In-111 ProstaScint ® uptake. Though ProstaScint ® uptake in renal cell carcinoma and in metastatic aortocaval lymph nodes from prostate cancer may be seen in clinical practice, this combination has not been reported previously.